Tectonostratigraphic evolution of the Nellore schist belt, southern India, since the Neoarchaean - Saha, D.; Sain, A.; Nandi, P.; Mazumder, Rajat; Kar, R. (Geological Society, 2015)
Tectonostratigraphic development of the c. 300 km-long Nellore schist belt (NSB) of southern India is described in relation to the post-Neoarchaean growth of the Dharwar cratonic nucleus. Lying along the eastern margin of the Dharwar cratonic nucleus, the NSB comprises several geologically and geochemically distinct tracts of deformed Palaeoproterozoic to Mesoproterozoic volcanosedimentary successions: the Vinjamuru Group, the Kandra ophiolite complex (KOC), the Kanigiri ophiolitic melange (KOM) and the Udaigiri Group, arranged in relative order of younging. The high-grade Eastern Ghats belt occurs further to the east of the NSB with a tectonic contact. Thrust-transported oceanic crust remnants occur in the 1.9 Ga KOC, 1.34 Ga KOM, and the Vinjamuru Group, which show multiple deformation, amphibolite facies metamorphism and granitic intrusions. The available geological, geochemical and geochronological data have been examined to tentatively constrain the relative age of the different tectonostratigraphic units of the NSB, tectonic juxtaposition and implications in relation to global events in the Proterozoic. Subduction-related ocean closures outboard and east of the Dharwar Craton, evidenced by the KOC and KOM, possibly had links with the assembly of Columbia and its final dispersal, respectively.